2011
DOI: 10.1029/2011gl048239
|View full text |Cite
|
Sign up to set email alerts
|

Capillary heterogeneity trapping of CO2 in a sandstone rock at reservoir conditions

Abstract: [1] The storage of CO 2 in deep subsurface porous rocks is being developed worldwide for the mitigation of emission from large industrial sources such as power plants and steel manufacturing. A main concern of this technology is in ensuring that the upwardly buoyant CO 2 does not migrate to the surface. Simulation studies suggest that substantial amounts of CO 2 can be trapped within permeable sections of a reservoir by capillary forces and intra-reservoir heterogenities, but there is little experimental obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(152 citation statements)
references
References 26 publications
7
142
0
3
Order By: Relevance
“…The effectiveness of this mechanism has been demonstrated experimentally. In a CO 2 flooding column experiment, it was found that a thin layer of reduced porosity at the exiting end of the column greatly increases (by a factor of 2-5 times) the residual CO 2 trapping in the core [123].…”
Section: Effect Of Reservoir Heterogeneitymentioning
confidence: 99%
“…The effectiveness of this mechanism has been demonstrated experimentally. In a CO 2 flooding column experiment, it was found that a thin layer of reduced porosity at the exiting end of the column greatly increases (by a factor of 2-5 times) the residual CO 2 trapping in the core [123].…”
Section: Effect Of Reservoir Heterogeneitymentioning
confidence: 99%
“…For lower permeability media, residual trapping is expected to increase as the CO 2 residual saturation S gr increases. S gr is a history-dependent property that is correlated to the maximum historical CO 2 saturation S gmax , and the maximum possible CO 2 residual saturation S grmax , a fixed material property, through the Land 16 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pore-and micro-scale transport properties of sandstone reservoirs have been well characterized in the petrophysics literature [10][11][12][13], as sandstones contain a large portion of global petroleum reserves [10]. Recently, carbonate saline aquifers have been identified as suitable carbon dioxide sequestration sites due to their high porosity, effective stratigraphic trapping, and global abundance [14,15].…”
Section: Introductionmentioning
confidence: 99%